IMPLEMENTASI ETIKA PELAYANAN PADA MINI MARKET DAN SWALAYAN PANYABUNGAN KABUPATEN MANDAILING NATAL GUNA MENCAPAI PROFIT YANG MAKSIMAL DITINJAU DARI EKONOMI ISLAM - Jureid Jureid (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2020)
Ethics must be a priority for the company or employees in every activity, including in achieving maximum profit. mini markets and supermarkets as a semi-modern place should not only make profit as its main orientation but to priority ethics as its first step gaining maximum profit. The purpose of this study was to determine the implementation of ethics of service in mini markets and supermarkets in Panyabungan Mandailing Natal in order to achieve maximum profit and to overview the efforts to achieve profit in accordance with ethics of service in the view of Islamic economics. This research method is descriptive qualitative. This research concludes that mini markets and supermarkets in Panyabungan have implemented service ethics based on indicators of honesty values, speaking politely, skillfully, serving friendly, not prejudiced, serving responsibly, employees also apply helpful attitude, serve consumers well without favoritism and neatly dressed. Overview of Islamic Economics on the implementation of service ethics is in accordance with the principles of Islamic economics, namely the value of justice and balance in every practice. Justice, balance, honesty, help and the value of other sharia maqasid as Islamic economic values has been carried out with these indicators, all of which are in accordance with the principles of implementing Islamic economic values or Islamic law.